Improvement of Flame Retardant Properties of Polyurethane Composites Using Microencapsulation Technology. Issue 3 (11th February 2019) - Chen, Chin-Hsing; Chiang, Chin- Lung
ABSTRACT: One kind of microencapsulated flame retardant containing melamine polyphosphate(MPP) and hydrophobic resin layer as core and shell material was synthesized by in situ polymerization technology. The structures and properties of microencapsulated MPP were characterized by Fourier transform infrared spectroscopy, scanning electron microscopy and water contact angle. Thermal behaviors of the composites containing microencapsulated MPP were analyzed by thermogravimetric analysis. Flame retardant tests indicated that the microencapsulated MPP with the polymer resin led to an improvement of the hydrophobicity. Results revealed that the flame retardancy of the composites was improved at the same fillers loading through the microencapsulation technology, which the char yields reached ( 26.9wt%) and flame retardance grade (LOI-38%) with optimized MPP addition ( 40%) to polymer matrix. GRAPHICAL ABSTRACT: